Priority and internet quality - Jörn Kruse (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2009)
The significant increase of internet traffic is to a large extent caused by more high-data-rate applications like file-sharing etc. Although network operators constantly increase router and line capacities, overload occurs from time to time, causing delays, jitter and packet-losses at the data packet level. At the service level this may significantly reduce the quality of certain applications. Among those are interactive services like VoIP, some business applications, online gaming etc. and other on-time-services like internet-television. This will result in systematic inefficiencies which can mainly be attributed to two reasons. The first one is the widespread use of internet-flatrates and the second one is a much too strict interpretation of the network neutrality principle. The latter describes the fact that every single data packet will be handled strictly equal at every router, no matter what application it belongs to and what the technical and economic consequences of delayed or dropped packets will be. A congestion model shows that flatrates which users' marginal outlays cause to be zero are inefficient as soon as positive marginal overload externalities exist. It comes up with a general pricing solution which will be questioned later on. In this framework, optimal internet capacity is identified and the networks' overprovisioning policy is found to be inefficient. The key issue for internet congestion problem is the fact that, although services are homogenous at the data packet level, they are very heterogenous at the service level. They are very different with respect to data rate, quality-sensitivity, and economic value. Under strict network neutrality rule it can be demonstrated that certain valuable, quality-sensitive services will be significantly harmed (and potentially be crowded out altogether) by non-qualitysensitive, high-data-rate services which may have low economic value. Giving priority to certain services in overload situations looks like the adequate solution to the problem. However, this always bears the risk of discriminating some service providers and applications and will be heavily debated. A more appropriate solution is provided by priority pricing, whereby users express their willingness to pay for priority treatment in case of an overload. Customers have an ex ante choice between different qualities of service. The choice of a service provider to pay for high priority (high quality of service) will depend mainly on two factors, the quality-sensitivity and the end-users' willingness to pay for such services. Only providers of quality-sensitive services will have any reason whatsoever to pay for traffic prioritization. Providers of non-quality-sensitive services (file sharing, e-mailing, webbrowsing) will be adequately served by best effort traffic and will thus obtain it cheaply. Priority pricing (quality of service) results in an economically efficient use of scarce router capacity according to the economic congestion effects of the specific service. It avoids the crowding-out problem. It allows to generate more economic value out of a given internet capacity.
urn:nbn:de:gbv:705-opus-20889
Keywords: L86; L96; 330; Internet; Quality of Service; Priority Pricing; Overprovisioning; Filesharing; Internet; Telekommunikationsnetz; Kapazitätsauslastung; Dienstleistungsqualität; Netzzugang; Spitzenlastpreis